CCR7 alterations associated with inferior outcome of adult T‐cell leukemia/lymphoma under mogamulizumab treatment. Issue 5 (6th September 2022) - Sakamoto, Yuma; Ishida, Takashi; Masaki, Ayako; Murase, Takayuki; Ohtsuka, Eiichi; Takeshita, Morishige; Muto, Reiji; Iwasaki, Hiromi; Ito, Asahi; Kusumoto, Shigeru; Nakano, Nobuaki; Tokunaga, Masahito; et al.
Abstract: Adult T‐cell leukemia/lymphoma (ATL) patients have a very poor prognosis. The humanized anti‐CCR4 therapeutic monoclonal antibody, mogamulizumab, is a key agent for ATL treatment. Our previous integrated molecular analysis demonstrated that among all the driver genes in ATL, CCR7 gene alterations were significantly associated with clinical response to mogamulizumab. Accordingly, here we investigated the detailed clinical impact of CCR7 alterations in a larger cohort of ATL patients. These CCR7 alterations, most of which lead to C‐terminus truncations, were observed in 27 of 223 patients (12%). For patients receiving mogamulizumab but not allogeneic hematopoietic stem cell transplantation (HSCT), CCR7 alterations were significantly associated with worse survival (median survival from the first dose of mogamulizumab of 0.7 years for 12 patients with CCR7 alterations vs. 1.6 years for 72 patients without, p = 0.020). On the other hand, the presence or absence of CCR7 alterations had no significant impact on survival in the entire cohort (median overall survival of 1.4 and 1.8 years, respectively, p = 0.901), or on the survival of patients receiving allogeneic HSCT (median survival from the day of transplantation of 0.9 years for 6 patients with CCR7 alterations and 1.4 years for 48 without, p = 0.543). Multivariate analysis indicated that patients with CCR4 alterations but lacking CCR7 alterations ( n = 20) had significantly better survival after receiving mogamulizumab‐containing treatments (hazard ratio for survival, 0.437, 95% confidence interval, 0.192–0.994). This study contributes to the establishment of precision medicine for ATL.